Earnings Inequality, the Spatial Concentration of Poverty, and the Underclass - Danziger, Sheldon; Gottschalk, Peter (American Economic Review, 2016)
William J. Wilson (1978, 1985, 1986) has hypothesized that the combination of increased spatial concentration and increased inequality of income among blacks has caused adverse behavioral consequences for poor blacks and contributed to the development of an underclass. Lessening segregation and the general rise in black economic well-being in the postwar period enabled middle-income blacks to move out of segregated inner-city neighborhoods. As a result, low-income blacks in these areas now rarely come in contact with middle-class blacks, who had previously influenced social organizations and community institutions, and provided role models of economic and social success. Wilson hypothesizes that poor blacks have changed their labor force and family behaviors because of the social and economic consequences of this selective outmigration. Wilson's hypothesis has both an empirical and a causal component. In this paper we focus primarily on the former. In the first two sections, we review changes in the level and distribution of male earnings, and in the spatial concentration of poverty. The trends for blacks are compared to those for whites. The third section discusses the links between the empirical evidence and the causal component-did these changes lead to behavioral responses that contributed to the development of an underclass?